Combinations for treating cancers - CLARKE ASTRID; DI PAOLO JULIE (2017)
Disclosed are combinations for treating a cancer in a subject (e.g., a human) in need thereof, comprising a therapeutically effective amount of a compound of formula (I): or a pharmaceutically acceptable salt thereof, and a vinca-alkaloid, or a pharmaceutically acceptable salt thereof. The subject may be very high risk or high risk for the cancer and may not respond to either agent administered as a sole therapy. The subject who has the cancer may also be refractory to at least one chemotherapy treatment, or is in relapse after treatment with chemotherapy, or both. The cancer may be a hematologic malignancy, such as leukemia or lymphoma, or a solid tumor cancer, such as pancreatic, lung and colon cancer. 本发明公开了在有需要的受试者(例如，人)中治疗癌症的组合，所述组合包括治疗有效量的式(I)的化合物或其药学上可接受的盐，以及长春花生物碱或其药学上可接受的盐。该受试者可处于癌症的非常高风险或高风险中，且不响应于作为单治疗给药的任何药物。患有癌症的受试者也可为至少种化疗治疗难以治愈的，或处于用化疗进行治疗后的复发中，或这二者。所述癌症可为恶性血液病如白血病或淋巴瘤，或实体瘤癌症如胰腺癌、肺癌和结肠癌。